An efficiency evaluation problem including fuzzy weights - Heydar, Maryam; Abu Bakar, Mohd Rizam; Mansourirad, Ehsanollah; Leong, Wah June; Senu, Norazak (Institute for Mathematical Research, Universiti Putra Malaysia, 2014)
This paper presents a procedure to dissolve a fuzzy weights CCR model with numerical input and output data in the objective function. This technique is a combination of utilizing fuzzy operations arithmetic and traditional method in DEA in order to convert the model into two simple linear programming problems with the purpose of detecting the effect of uncertain factors on the efficiency scores of decision making units (DMUs). It is in accordance with our determination to provide a method based on data envelopment analysis (DEA), supporting efficiency evaluation problems in fold fuzziness in factor weights to assist decision making issues.